Renal function protection and the mechanism of ginsenosides: Current progress and future perspectives - Fan, Meiling; Lan, Xintian; Wang, Qunling; Shan, Mengyao; Fang, Xiaoxue; Zhang, Yegang; Wu, Donglu; Luo, Haoming; Gao, Wenyi; Zhu, Difu (Frontiers in Pharmacology, 2023)
Nephropathy is a general term for kidney diseases, which refers to changes in the structure and function of the kidney caused by various factors, resulting in pathological damage to the kidney, abnormal blood or urine components, and other diseases. The main manifestations of kidney disease include hematuria, albuminuria, edema, hypertension, anemia, lower back pain, oliguria, and other symptoms. Early detection, diagnosis, and active treatment are required to prevent chronic renal failure. The concept of nephropathy encompasses a wide range of conditions, including acute renal injury, chronic kidney disease, nephritis, renal fibrosis, and diabetic nephropathy. Some of these kidney-related diseases are interrelated and may lead to serious complications without effective control. In serious cases, it can also develop into chronic renal dysfunction and eventually end-stage renal disease. As a result, it seriously affects the quality of life of patients and places a great economic burden on society and families. Ginsenoside is one of the main active components of ginseng, with anti-inflammatory, anti-tumor, antioxidant, and other pharmacological activities. A variety of monomers in ginsenosides can play protective roles in multiple organs. According to the difference of core structure, ginsenosides can be divided into protopanaxadiol (PPD) -type (including Rb1, Rb3, Rg3, Rh2, Rd and CK, etc.), and protopanaxatriol (PPT)- type (including Rg1, Rg2 and Rh1, etc.), and other types (including Rg5, Rh4, Rh3, Rk1, and Rk3, etc.). All of these ginsenosides showed significant renal function protection, which can reduce renal damage in renal injury, nephritis, renal fibrosis, and diabetic nephropathy models. This review summarizes reports on renal function protection and the mechanisms of action of these ginsenosides in various renal injury models.